Kepemilikan Institusional, Kompetensi CFO, Ketidakpastian Lingkungan dan Penghindaran Pajak - Dahlia Sari; Lolita Riantida Simamora (Owner : Riset dan Jurnal Akuntansi, 2025)
This research examines the relationship between institutional ownership and CFO competence in relation to tax avoidance, as well as the moderating role of environmental uncertainty in tax avoidance behavior. The study utilizes a sample of 474 observations from publicly listed companies in the Indonesia Stock Exchange (BEI) during the period of 2016-2021. The findings of this study provide evidence that high levels of institutional ownership are associated with increased tax avoidance activities, while CFO competence is positively related to tax avoidance behavior. Moreover, the results demonstrate that environmental uncertainty weakens the negative relationship between institutional ownership and tax avoidance, while it strengthens the positive relationship between CFO competence and tax avoidance. These findings have implications for regulators to continuously improve tax regulations and consider implementing punishments as deterrents for corporate taxpayers engaged in tax avoidance practices.